"Serving God, Fatherland, and Language": Alcover, Catalan, and Science - Herrero, Agustín Ceba (Zygon, 2019)
This article intends to contribute to the science-religion historiography with two topics—philology and the construction of national identities—that can help provide a more complex picture of the relations between science and religion. We use the life and work of the Mallorcan Catholic priest Antoni Maria Alcover (1862-1932) as a case study that puts language, linguistics, and nationalism on the board of science and religion studies. Alcover was the main driving force of the Catalan Dictionary, a collective enterprise that set out to inventory the complete oral and literary lexicon of this language, and which mobilized thousands of people, many of which were clergymen, from all over the Catalan-speaking territories. In the article, we will explore Alcover's education; the way he established a link between language, religion, and fatherland; the shaping of his identity as a philologist in the image mainly of new German notions and practices; as well as his role in the institutionalization process of the Catalan language as a scientific language, as a language for science and for religion.